The Role of Leadership, Ethical Behavior, and Market Orientation in Improving Social Entrepreneurship Outcomes and Impact on Local Communities in Indonesia - Nur Hasan Kurniawan; Koesmawan Koesmawan; Yana Priyana (Jurnal Wacana Ekonomi, 2025)
Social entrepreneurship has become a potent tool for bringing about positive change in local communities, particularly in developing nations like Indonesia. The present study employs a quantitative approach to investigate the significance of leadership, ethical conduct, and market orientation in propelling the outcomes of social entrepreneurship and their influence on nearby communities. The study employs structural equation modeling (SEM) with partial least squares (PLS-SEM) to examine the correlations between these factors. It is based on a sample of 468 social enterprises and organizations. Results showed that Improving the results of social entrepreneurship and its influence on regional communities primarily depends on effective leadership, which encompasses both transformational and transactional approaches. Transparency, accountability, and social responsibility are the cornerstones of ethical behavior, closely linked to improved social entrepreneurship outcomes and increased community well-being. Market orientation dramatically enhances the results of social entrepreneurship and its influence on the community. It encompasses market research, customer feedback, and market-based strategy. The study's findings offer the potential to improve social entrepreneurship theory, which strongly emphasizes market responsiveness, ethical principles, and leadership. Furthermore, this study provides valuable implications for stakeholders, policymakers, and social entrepreneurs who wish to use social entrepreneurship projects to promote positive social change. Social companies can optimize their impact by allocating resources towards leadership development, instituting ethical norms, prioritizing market research, and taking a comprehensive strategy.